Proceedings of the 31st Conference on Winter Simulation Simulation---a Bridge to the Future - WSC '99 1999
DOI: 10.1145/324898.325049
|View full text |Cite
|
Sign up to set email alerts
|

Operative requirements and advances for the new generation simulators in multimodal container terminals

Abstract: The paper outline the evolution of container terminal requirements for simulation and the potential of new advanced techniques in the integration with these aspects; the authors present application examples and experimental results that maximized the impact of these new concepts in real complex port realities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…In this respect, Cargo Systems in 1999 acknowledged that simulation is fundamental and the most used form of simulation in port processes is the stochastic discrete-event model, though combined simulation is being used in particular cases (Bruzzone et al, 1999). The port industry, like shipping, is a very risky, capital intensive industry whose return on assets can only be assessed in a long-term perspective.…”
Section: S I M U L At I O Nmentioning
confidence: 99%
See 2 more Smart Citations
“…In this respect, Cargo Systems in 1999 acknowledged that simulation is fundamental and the most used form of simulation in port processes is the stochastic discrete-event model, though combined simulation is being used in particular cases (Bruzzone et al, 1999). The port industry, like shipping, is a very risky, capital intensive industry whose return on assets can only be assessed in a long-term perspective.…”
Section: S I M U L At I O Nmentioning
confidence: 99%
“…There is, however, a lack of research regarding the productivity of the overall process and subsequent decision-making. Bruzzone et al (1999) goes further and identifies a list of future port requirements that can be addressed by computer simulation. Simulation helps container terminal operators, harbour planners, port authorities, and consulting companies to evaluate the dynamic processes of container terminals.…”
Section: S I M U L At I O Nmentioning
confidence: 99%
See 1 more Smart Citation
“…Little understanding exists regarding the differences and similarities between the two simulation approaches, let alone understanding when should one approach be used instead of the other. As general rule of thumb is possible to use both approaches for modeling any system as proven by the Authors in many works [2] [3][8] however one issue is to "build" a simulation model another is to "extract knowledge" from a model in which the modeling strategies are playing a crucial role.…”
Section: Introductionmentioning
confidence: 99%
“…The decision is based on a cost model including fixed investment costs and variable operation costs. Bruzzone et al (1999Bruzzone et al ( , 1243 have demonstrated the effectiveness of a simulation model for supporting complex container port management. Saanen (2000) and Saanen et al (2003) have used simulation models to account for the cost values of different types of equipment to be installed at a terminal.…”
Section: Introductionmentioning
confidence: 99%